2019
DOI: 10.22616/foodbalt.2019.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various packaging solutions on the quality of hazelnuts in nut–dried fruit mixes

Abstract: Nut-dried fruit mixes are a nutritious snack, which can be consumed throughout the year. However, moisture migration, which occurs between components with higher moisture content (dried fruit) and lower moisture content (cereals, nuts), can lead to undesirable physical and chemical changes during storage. The aim of this study was to identify optimal packaging solutions for various types of nut and dried fruit mixes in order to maintain the quality of hazelnuts. Experiments were carried out at the laboratories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…To this aim, hazelnut perisperm was firstly powdered and melt compounded at two different loading levels (5 and 10 wt%) in a commercial bioderived and biodegradable polymer matrix (Ecovio ® , by BASF) based on poly (butylene adipate-co-terephthalate) (PBAT) and PLA. This matrix was selected based on literature findings indicating that PLA is one of the most suitable packaging materials to preserve quality of nut-dried fruits [ 22 ]. The blends were used to produce films in different processing conditions on a pilot-scale film-blowing extrusion plant.…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, hazelnut perisperm was firstly powdered and melt compounded at two different loading levels (5 and 10 wt%) in a commercial bioderived and biodegradable polymer matrix (Ecovio ® , by BASF) based on poly (butylene adipate-co-terephthalate) (PBAT) and PLA. This matrix was selected based on literature findings indicating that PLA is one of the most suitable packaging materials to preserve quality of nut-dried fruits [ 22 ]. The blends were used to produce films in different processing conditions on a pilot-scale film-blowing extrusion plant.…”
Section: Introductionmentioning
confidence: 99%
“…The total colour difference (ΔE) was calculated according to the equation Nr. 3 [ 34 , 35 ]. where: L *—colour intensity (light-dark) in extrudate; —colour intensity (light-dark) in the initial material; a *—green-red colour component in the extrudate; —green-red colour component in the initial material; b *—blue-yellow colour component in the extrudate; and —blue-yellow colour component in the initial material.…”
Section: Methodsmentioning
confidence: 99%
“…Scientific studies have proven that recycled plastics can be used for packaging materials, thus not causing pollution by accumulating a large amount of waste that adversely affects the existence of our planet's ecosystem. Therefore, companies are willing to invest in the use of more eco-friendly plastics that can be used as bio-based packaging material that may store packaged products and take advantage of residues that would be discarded otherwise as well as increase the storage time of foods products (Dutta & Sit, 2022;Kirse-Ozolina, Muizniece-Brasava & Veipa, 2019). Scientists from France evaluated the latest published scientific studies and concluded that the most advanced technologies in the field of packaging clearly have a greater demand for the latest eco-friendly packaging materials with greater efficiency in maintaining the food quality and safety during storage.…”
Section: Introductionmentioning
confidence: 99%